The genetics of the skin barrier in eczema and other allergic disorders. Issue 5 (October 2015) - Marenholz, Ingo; Esparza-Gordillo, Jorge; Lee, Young-Ae
Abstract : Purpose of review: We summarize current knowledge on the genetic determinants of skin barrier deficiency in relation to eczema and disease progression to other allergic manifestations. Recent findings: There is increasing evidence that impairment of epidermal barrier function is not only a risk factor for the development of eczema but also for disease progression to allergic airway disease and food allergy. Support comes from recent association studies linking genetic variants in epidermal genes with eczema and food allergy, from monogenic diseases with severe skin barrier defects which display multiple allergic manifestations, and from mouse models providing a mechanism from skin inflammation to allergic reactions in the lung and intestine. Summary: The key role of the skin barrier defect in the development of eczema and eczema-associated allergic diseases may have important implications for prevention and treatment strategies. Initial clinical trials with moisturizing creams revealed promising results for the prevention of eczema in early infancy. Their long-term effects will be critical to demonstrate the potential benefit of barrier repair therapy in allergic disease prevention.